Urban vulnerability and the contribution of socio-environmental fragmentation: Theoretical and methodological pathways. (August 2017) - Krellenberg, Kerstin; Welz, Juliane; Link, Felipe; Barth, Katrin
As ongoing parallel processes, urbanization and climate change call for overarching context-specific responses that tackle the complex challenges involved and include a comprehensive data base to identify the most pressing action needs. We argue that urban vulnerabilities must take centre stage in this regard. What comes to the fore in the context of urban vulnerability to climate-related hazards is the interaction of human systems with the environment. Understanding the impact of changes in temperature and precipitation on socio-ecological systems is therefore not enough. Insights into the complexity of urban development, social inequalities, economics and politics are needed. To address this complexity, the article focuses on the challenges associated with socio-environmental fragmentation patterns and residential vulnerability, since the interlinkages between them contribute substantially to furthering insights into the specifics of 'urban' vulnerabilities to climate-related hazards. An approach that combines socio-environmental fragmentation and residential vulnerability is presented. This approach explores socio-environmental urban developments as well as individual perceptions and capacities.